COVID-19 pandemic: Case studies and perspectives - Liu, Michael (Side Effects of Drugs Annual, 2020)
As of September 9, 2020, Worldwide coronavirus disease 2019 (COVID-19) has caused 894 000 deaths with over 27.5 million confirmed cases. There is an urgent need for effective treatment. Considerable efforts have been placed on developing novel therapeutics, including antivirals and vaccines. Current management of COVID-19 is supportive, with several experimental drugs. Respiratory failure from acute respiratory distress syndrome overshadowed by severe cytokine storm appears to be the leading cause of mortality. This article has reviewed several unique case studies published from December 2019 through July 31, 2020 with the above perspectives.